Method for recovering silicon and metal from waste catalytic cracking / catalytic cracking catalyst
By carrying out hydrochloric acid leaching treatment and hydrofluoric acid-sodium hydroxide reaction on the waste catalytic cracking/catalytic cracking catalyst, the problem of efficient recovery of silicon and metal in the waste catalyst is solved, and high recovery rate and high purity silicon and metal products are achieved, with good controllability and environmental protection benefits.
Patent Information
- Application Number
- CN202311264350.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-01
AI Technical Summary
The prior art is difficult to efficiently recover silicon and metals in waste catalytic cracking/catalytic cracking catalysts at the same time, and especially silicon, the recovery and purity of silicon are difficult to reach the ideal level.
By leaching the spent catalytic cracking/catalytic cracking catalyst at a specific concentration of hydrochloric acid at a specific temperature, loose microspheres with high silicon content are obtained, and the reaction of hydrofluoric acid and sodium hydroxide is used to completely or nearly complete the silicon into the gas phase, and finally a high-purity liquid-phase silicon product is formed.
The efficient recovery of silicon and metal in waste catalytic cracking/catalytic cracking catalyst is achieved, and the recovery rate of silicon reaches 95%, while ensuring efficient recovery of metals, good product controllability, and dual advantages of economic benefits and environmental protection.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oil refining catalysts and relates to a method for recovering silicon and metal from waste catalytic cracking / catalytic cracking catalysts. Background Art
[0002] Catalytic cracking / catalytic cracking is an important oil refining process that converts heavy oil and crude oil into finished oil such as gasoline and diesel or basic chemical raw materials such as ethylene and propylene. At present, most industrial catalytic cracking / catalytic cracking units use fast fluidized bed (riser) reactors and use microsphere catalysts with an average particle size of 60-80μm. With the long-term operation of catalytic cracking / catalytic cracking equipment, the content of heavy metals Ni, V, coke, and alkali metals continues to increase, resulting in a continuous decrease in catalyst activity, selectivity, hydrothermal stability, and conversion rate. It is usually impossible to achieve activity balance by adding fresh catalyst. It is necessary to discharge the used catalyst from the equipment in a timely manner and replace it with fresh catalyst. The discharged catalyst is called spent catalytic cracking / catalytic cracking catalyst.
[0003] There are three main sources of spent catalytic cracking / catalytic cracking catalysts: the most important source is that during the operation of the catalytic cracking / catalytic cracking equipment, the catalyst activity is reduced due to the poisoning of high temperature and heavy metals and cannot meet the requirements of the catalytic cracking / catalytic cracking reaction. In order to maintain the catalyst in the equipment at a certain activity, fresh agents are regularly added and some deactivated catalysts are removed from the regenerator; the second is fine particles with a particle size of less than 20 μm generated by factors such as collision or thermal collapse between the catalyst and the high-speed logistics (main air and crude oil), container wall and catalyst particles in the equipment. These particles cannot be collected by the first and second stage cyclone separators, but can be collected by the subsequent third stage cyclone separator. These spent catalysts are the third cyclone fine powder; the third source is the ultrafine catalyst powder collected from the flue gas desulfurization and denitrification sludge during the flue gas purification process. The chemical composition of spent catalytic cracking / catalytic cracking catalysts includes aluminum oxide, silicon oxide, rare earth, nickel, vanadium, etc., and the typical content is shown in Table 1.
[0004] Table 1. Chemical composition of spent catalytic cracking / catalytic cracking catalyst
[0005] project <![CDATA[ω(Al2O3),%]]> <![CDATA[ω(SiO2),%]]> <![CDATA[ω(RE2O3),%]]> ω(Ni), μg / g ω(V), μg / g Waste Catalyst 43.5 46.4 4.5 7200 2500
[0006] According to statistics, the world produces about 500,000 tons of spent FCC / Cracking catalysts every year, and the amount continues to grow at an annual rate of 5%. At present, the most common way to deal with spent FCC / Cracking catalysts is to bury them. Since spent FCC / Cracking catalysts contain heavy metal elements such as Ni, V, and rare earths, burying them will inevitably lead to a large amount of waste of effective resources and cause pollution to the ecological environment.
[0007] In recent years, researchers have proposed some recovery methods for waste catalytic cracking / catalytic cracking catalysts to recover Ni, V, rare earth, Al and other metals in waste catalytic cracking / catalytic cracking catalysts. However, there is a common problem that only the recovery rate and purity of one or two metals can be guaranteed, and the recovery rate and purity of various metals cannot be taken into account at the same time.
[0008] Silicon is an important resource and chemical raw material with a wide range of uses, almost covering all walks of life, such as traditional petrochemical industry, high-tech fields, light industry, textile industry, machinery industry, construction industry, agriculture, etc. However, the current waste catalytic cracking / catalytic cracking catalyst recovery technology mainly focuses on the recovery of metals such as Ni, V, rare earth, and Al, and there is no mature technology to achieve the recovery of silicon in waste catalytic cracking / cracking catalysts.
[0009] In summary, there is still a need to study the recovery technology of spent catalytic cracking / catalytic cracking catalysts in order to achieve efficient recovery of silicon and metals at the same time. Summary of the invention
[0010] The object of the present invention is to provide a technical solution that can simultaneously realize efficient recovery of silicon and metal. In order to achieve the above object, the present invention provides the following technical solution.
[0011] The present invention provides a method for recovering silicon and metals from spent catalytic cracking / catalytic cracking catalysts, wherein the method comprises:
[0012] The spent catalytic cracking / catalytic cracking catalyst is treated with hydrochloric acid having a concentration of 1-3 mol / L (based on the volume of the hydrochloric acid) at 60-120° C., and a leachate and loose microspheres are obtained by solid-liquid separation;
[0013] Utilizing leachate for metal recovery;
[0014] The loose microspheres react with a hydrofluoric acid solution, and the generated gas is introduced into a sodium hydroxide solution for reaction, and the solid phase is removed from the product obtained by the reaction to obtain liquid sodium silicate; wherein the mass concentration of HF in the hydrofluoric acid solution is 5-47% (based on the total mass of the hydrofluoric acid solution as 100%), and the mass concentration of sodium hydroxide in the sodium hydroxide solution is 5-40% (based on the total mass of the sodium hydroxide solution as 100%).
[0015] The method for recovering silicon and metals from waste catalytic cracking / catalytic cracking catalysts provided by the present invention is to subject the waste catalytic cracking / catalytic cracking catalysts to acid leaching with hydrochloric acid of a specific concentration at a specific temperature, thereby achieving complete or nearly complete leaching of Ni, V, rare earth, and Al components in the waste catalytic cracking / catalytic cracking catalysts into the leachate and obtaining loose microspheres with high silicon content and large porosity (wherein the silicon component is completely or nearly completely retained in the loose microspheres), and then utilizing the loose microspheres to react with a hydrofluoric acid solution to allow the silicon to completely or nearly completely enter the generated gas phase, and the gas phase is passed into a sodium hydroxide solution to produce a high-purity liquid phase silicon product. Loose microspheres are a type of liquid silicon product with a very high silicon content (which can reach more than 98.5%) and a very high porosity (which can reach 0.9 cm 3 / g or more), loose microspheres with large silicon exposed surface area, which lays the foundation for efficient and high-purity recovery of silicon. In summary, the method for recovering silicon and metals from spent catalytic cracking / catalytic cracking catalysts provided by the present invention realizes efficient and high-purity recovery of silicon through acid leaching treatment with hydrochloric acid of a specific concentration at a specific temperature, treatment with hydrofluoric acid solution of a specific concentration, and treatment with sodium hydroxide of a specific concentration, and the recovery rate of silicon can reach 95%; at the same time, acid leaching treatment with hydrochloric acid of a specific concentration at a specific temperature and treatment with hydrofluoric acid solution can completely or nearly completely leach Ni, V, rare earth, and Al components into the leachate, laying the foundation for efficient recovery of Ni, V, rare earth, and Al components.
[0016] Preferably, based on the total mass of the spent catalytic cracking / catalytic cracking catalyst as 100%, the mass content of SiO2 in the spent catalytic cracking / catalytic cracking catalyst is 40-50wt%, and the mass content of SiO2, Al2O3, RE2O3, Ni, and V is not less than 99.5wt%;
[0017] More preferably, based on the total mass of the spent catalytic cracking / catalytic cracking catalyst as 100%, the mass content of SiO2 in the spent catalytic cracking / catalytic cracking catalyst is 40-50wt%, the mass content of Al2O3 is 40-50wt%, the mass content of RE2O3 is 0.1-10wt%, the mass content of Ni is 0.01-2wt%, and the mass content of V is 0.01-2wt%.
[0018] Preferably, the spent catalytic cracking / catalytic cracking catalyst is pulverized before being subjected to hydrochloric acid leaching treatment, and is then pulverized into a material with a particle size of 1-15 μm before being subjected to hydrochloric acid leaching treatment.
[0019] Preferably, the hydrochloric acid pickling treatment time is 4-24h.
[0020] Preferably, the silicon oxide content of the loose microspheres is not less than 98.5wt% (based on the total mass of the loose microspheres as 100%), and the porosity is not less than 0.9cm 3 / g.
[0021] Preferably, based on the total mass of the loose microspheres being 100%, the total mass content of rare earth, aluminum, nickel and vanadium in the loose microspheres is less than 1.5 wt%.
[0022] Preferably, the mass concentration of HF in the hydrofluoric acid solution is 15-25% (based on the total mass of the hydrofluoric acid solution being 100%).
[0023] Preferably, the temperature for the reaction of the loose microspheres with the hydrofluoric acid solution is 20-80°C.
[0024] Preferably, the reaction time of the loose microspheres and the hydrofluoric acid solution is 0.1-1 h.
[0025] Preferably, the reaction of the loose microspheres with the hydrofluoric acid solution is carried out under stirring conditions at a stirring speed of 300-600 rpm.
[0026] Preferably, the reaction of the loose microspheres and the hydrofluoric acid solution is carried out in a closed polytetrafluoroethylene-lined high-pressure reactor; wherein the total loading amount of the loose microspheres and the hydrofluoric acid solution in the polytetrafluoroethylene-lined high-pressure reactor is 1 / 5-1 / 3 of the volume of the reactor, and the pressure in the polytetrafluoroethylene-lined high-pressure reactor during the reaction of the loose microspheres and the hydrofluoric acid solution is 0.1-20 MPa.
[0027] Preferably, the mass concentration of sodium hydroxide in the sodium hydroxide solution is 10-25% (based on the total mass of the sodium hydroxide solution as 100%).
[0028] Preferably, the temperature at which the generated gas is introduced into the sodium hydroxide solution for reaction is 60-100°C.
[0029] Preferably, the generated gas is passed into the sodium hydroxide solution for a reaction time of 0.2-2 hours.
[0030] Preferably, the generated gas is passed into a sodium hydroxide solution for reaction in a closed high-pressure reactor.
[0031] Preferably, the method further comprises: removing the solid phase to obtain the liquid sodium silicate, concentrating, adjusting with alkali solution and re-filtering to obtain a sodium silicate solution product meeting the modulus and concentration requirements;
[0032] More preferably, the concentration is carried out at 85-105° C. for 1 h;
[0033] More preferably, the alkali solution is adjusted to a pH value of 12-13;
[0034] More preferably, the modulus of the sodium silicate solution product is 1.5-3.5;
[0035] More preferably, the SiO2 mass concentration in the sodium silicate solution product is 15-25wt%.
[0036] Preferably, the metal recovery using the leaching solution comprises:
[0037] The leaching solution is mixed with the oxalic acid solution and the pH value is adjusted to 1.6-2.3 by using an alkali solution for reaction, and the oxalic acid rare earth salt precipitate and the first filtrate are obtained through solid-liquid separation to realize rare earth recovery;
[0038] The first filtrate is subjected to extraction to recover vanadium, thereby obtaining a vanadium-rich extract and an extraction residue, thereby achieving vanadium recovery;
[0039] The pH value of the extract residue is adjusted to 6-10 by using alkaline solution to react, and a mixed precipitate of aluminum hydroxide and nickel hydroxide is obtained by solid-liquid separation;
[0040] Adding alkaline solution to the mixed precipitate of aluminum hydroxide and nickel hydroxide to adjust the pH value to 12-13 for reaction, and performing solid-liquid separation to obtain nickel hydroxide precipitate and aluminate solution, thereby realizing the recovery of nickel and aluminum;
[0041] More preferably, the method further comprises: evaporating the vanadium-rich extract to dryness, pyrolyzing and roasting to obtain vanadium pentoxide.
[0042] Preferably, the concentration of oxalic acid in the oxalic acid solution is 0.1-0.5 mol / L (based on the volume of the oxalic acid solution).
[0043] Preferably, the alkali solution used in the process of adjusting the pH value to 1.6-2.3 using alkali solution is ammonia water and / or sodium hydroxide solution.
[0044] Preferably, the extracting liquid used in the process of extracting and recovering vanadium from the first filtrate is an organic extracting liquid; more preferably, the extracting liquid may include but is not limited to at least one of (2-ethylhexyl) phosphate and ethylhexyl mono-2-ethylhexyl phosphate.
[0045] Preferably, in the process of extracting and recovering vanadium from the first filtrate, the volume ratio of the extract to the first filtrate is 1-3:1.
[0046] Preferably, the extraction time during the process of extracting and recovering vanadium from the first filtrate is 30-90 minutes.
[0047] Preferably, the alkali solution used in the process of adjusting the pH value of the extraction residue to 6-10 by using alkali solution can include but is not limited to at least one of sodium hydroxide solution, potassium hydroxide solution and ammonia water.
[0048] Preferably, the alkali solution used in the process of adding alkali solution to the mixed precipitate of aluminum hydroxide and nickel hydroxide to adjust the pH value to 12-13 can include but is not limited to at least one of sodium hydroxide solution, potassium hydroxide solution and ammonia water.
[0049] The technical solution provided by the present invention is to subject the waste catalytic cracking / catalytic cracking catalyst to acid leaching treatment with hydrochloric acid of a specific concentration at a specific temperature, thereby achieving complete or nearly complete liquid phase recovery of Ni, V, rare earth and Al in the waste catalytic cracking / catalytic cracking catalyst and obtaining loose microspheres with high silicon content, large porosity and large silicon exposed surface area (wherein the silicon component is completely or nearly completely retained in the loose microspheres); then the loose microspheres are mixed with hydrofluoric acid of a specific concentration, and a large number of accessible silicon species in the loose microspheres react deeply with the hydrofluoric acid to generate silicon tetrafluoride gas, SiO2+4HF=SiF4(gas)+2H2O, thereby achieving the goal of allowing all or nearly all silicon species to enter the gas phase; and then the silicon tetrafluoride gas is reacted with a sodium hydroxide solution of a specific concentration to generate sodium fluoride and sodium silicate, SiF4+6NaOH=Na2SiO3+4NaF+3H2O, and the reaction product is concentrated to precipitate NaF solid, and then a high-purity sodium silicate solution is obtained by solid phase removal. Compared with conventional waste catalytic cracking / catalytic cracking catalyst recovery methods, the technical solution provided by the present invention simultaneously realizes efficient recovery of silicon and metals (the recovery rates of silicon and metals can both reach a high level). The technical solution provided by the present invention has good controllability, realizes full recovery of waste catalytic cracking / catalytic cracking catalysts, and has the dual advantages of economic benefits and environmental protection. DETAILED DESCRIPTION
[0050] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0051] Sources of raw materials involved in the examples and comparative examples of the present invention:
[0052] Waste catalytic cracking / cracking catalyst 1: industrial grade, provided by Lanzhou Petrochemical Company; taking the total mass of the waste catalytic cracking / catalytic cracking catalyst as 100%, the mass content of SiO2 in the waste catalytic cracking / catalytic cracking catalyst is 46wt%, the mass content of Al2O3 is 46.5wt%, the mass content of RE2O3 is 5wt%, the mass content of Ni is 1.2wt%, and the mass content of V is 1wt%.
[0053] Waste catalytic cracking / cracking catalyst 2: industrial grade, provided by Lanzhou Petrochemical Company; based on the total mass of the waste catalytic cracking / catalytic cracking catalyst as 100%, the mass content of SiO2 in the waste catalytic cracking / catalytic cracking catalyst is 42wt%, the mass content of Al2O3 is 47.6wt%, the mass content of RE2O3 is 8wt%, the mass content of Ni is 1.4wt%, and the mass content of V is 0.8wt%.
[0054] Waste catalytic cracking / cracking catalyst 3: industrial grade, provided by Lanzhou Petrochemical Company; taking the total mass of the waste catalytic cracking / catalytic cracking catalyst as 100%, the mass content of SiO2 in the waste catalytic cracking / catalytic cracking catalyst is 49wt%, the mass content of Al2O3 is 44.5wt%, the mass content of RE2O3 is 4wt%, the mass content of Ni is 1.5wt%, and the mass content of V is 0.9wt%.
[0055] Waste catalytic cracking / cracking catalyst 4: industrial grade, provided by Lanzhou Petrochemical Company; based on the total mass of the waste catalytic cracking / catalytic cracking catalyst as 100%, the mass content of SiO2 in the waste catalytic cracking / catalytic cracking catalyst is 44wt%, the mass content of Al2O3 is 50wt%, the mass content of RE2O3 is 3wt%, the mass content of Ni is 1.7wt%, and the mass content of V is 1.2wt%.
[0056] Hydrofluoric acid solution: industrial grade, HF concentration 40wt%, density 1.15g / cm 3 .
[0057] Sodium hydroxide: industrial grade, purity 99wt%, density 2.13g / cm 3 .
[0058] Oxalic acid: industrial grade, purity 99.6wt%, density 1.77g / cm 3 .
[0059] Di(2-ethylhexyl) phosphate: industrial grade, purity 99wt%, density 1.13g / cm 3 .
[0060] Ethylhexyl phosphate mono-2-ethylhexyl ester: industrial grade, purity 99wt%, density 1.12g / cm 3 .
[0061] The present invention relates to the analysis method:
[0062] Analysis of elemental content of samples: XRF analysis was used for elemental analysis of solid samples, specifically using a ZSX Primus X-ray fluorescence spectrometer produced by Rigaku Corporation of Japan. The X-ray tube was an Rh target with good excitation efficiency for heavy and light elements. The current of the X-ray tube was 50mA, the voltage was 50kV, the field aperture diameter was 20mm, and the attenuation was 1. ICP analysis was used for elemental analysis of liquid samples, specifically using a Plasma2000 inductively coupled plasma-atomic emission spectrometer produced by China Iron and Steel Research Institute NAK Co., Ltd. The elemental content was determined after the analysis samples were diluted and fixed to volume.
[0063] Example 1
[0064] This embodiment provides a method for recovering silicon and metals from spent catalytic cracking / catalytic cracking catalysts, wherein the method comprises:
[0065] 1.0 kg of spent catalytic cracking / cracking catalyst 1 was subjected to physical sand milling to obtain material A1 with an average particle size of 10 μm.
[0066] Transfer material A1 to a polytetrafluoroethylene lined reactor (I), add 1.5 kg of 3 mol / L hydrochloric acid solution, react at 90°C for 10 h, and separate the product obtained by the reaction into a liquid phase leachate and a solid phase material B1; wherein rare earth, vanadium, nickel, and aluminum elements in the spent catalytic cracking / cracking catalyst are dissolved in the leachate, and silicon remains in material B1. Material B1 is a loose microsphere with a silicon content of 99.0 wt% and a porosity of 0.95 cm 3 / g, and the total mass content of rare earth, aluminum, nickel and vanadium is 1.0wt%.
[0067] 0.2 kg of oxalic acid solution with an oxalic acid concentration of 0.3 mol / L was added to the leaching solution, and the pH value was adjusted to 2 with ammonia water to generate oxalic acid rare earth salt precipitate, which was filtered to obtain the oxalic acid rare earth salt precipitate and the first filtrate to achieve rare earth recovery; analysis showed that the rare earth recovery rate was 96% and the purity of the rare earth oxalate was 99.7%.
[0068] Add di(2-ethylhexyl) phosphate extract (the volume ratio of di(2-ethylhexyl) phosphate extract to the first filtrate is 2:1) to extract for 60 minutes to obtain a vanadium-rich extract and an extract residue; evaporate the vanadium-rich extract at 100° C. for 4 hours and roast at 580° C. for 6 hours to obtain vanadium pentoxide, thereby recovering vanadium; analysis shows that the vanadium recovery rate is 96% and the vanadium pentoxide concentration is 99.5%.
[0069] A sodium hydroxide solution having a sodium hydroxide concentration of 2.5 wt % is added to the extract residue (aqueous phase) to adjust the pH value to 8, thereby generating a mixed precipitate of aluminum hydroxide and nickel hydroxide. After filtering, the sodium hydroxide solution is continuously added to the precipitate and the pH value is adjusted to 13 by stirring, and then filtered again. The precipitate is nickel hydroxide, and the filtrate is a sodium aluminate solution, thereby realizing the recovery of nickel and aluminum. According to analysis, the recovery rates of nickel and aluminum are 95% and 97% respectively, the purity of nickel hydroxide is 99.4%, and the purity of sodium aluminate is 99.5%;
[0070] Transfer material B1 to a polytetrafluoroethylene-lined autoclave (II), inject 3kg of HF solution with a concentration of 20wt%, react at 60℃ for 0.5h, and input the gas produced by the reaction into another polytetrafluoroethylene-lined autoclave (III) filled with 20kg of sodium hydroxide solution with a concentration of 15wt% through a one-way valve, and react at 80℃ for 1h. After the reaction, separate the product in the reactor (III) into solid and liquid to obtain solid sodium fluoride and crude sodium silicate liquid; the crude sodium silicate liquid is concentrated at 105℃ for 1h, adjusted to pH 12 with alkali solution, and then filtered to obtain 2.6kg of sodium silicate solution product with a modulus of 3 and a SiO2 mass concentration of 17wt%. After analysis and calculation, the silicon recovery rate is 97% and the purity of sodium silicate is 99.8%.
[0071] Example 2
[0072] This embodiment provides a method for recovering silicon and metals from spent catalytic cracking / catalytic cracking catalysts, wherein the method comprises:
[0073] 1.0 kg of spent catalytic cracking / cracking catalyst 2 was subjected to physical sand milling to obtain material A2 with an average particle size of 15 μm.
[0074] Transfer material A2 to a polytetrafluoroethylene lined reactor (I), add 1.5 kg of 2 mol / L hydrochloric acid solution, react at 80°C for 12 h, and separate the product obtained by the reaction into a liquid phase leachate and a solid phase material B2; wherein rare earth, vanadium, nickel, and aluminum elements in the spent catalytic cracking / cracking catalyst are dissolved in the leachate, and silicon remains in material B2. Material B2 is a loose microsphere with a silicon content of 98.8 wt% and a porosity of 0.97 cm 3 / g, and the total mass content of rare earth, aluminum, nickel and vanadium is 1.2wt%.
[0075] 0.15 kg of oxalic acid solution with an oxalic acid concentration of 0.4 mol / L was added to the leaching solution, and the pH value was adjusted to 1.8 with ammonia water to generate oxalic acid rare earth salt precipitate, which was filtered to obtain the oxalic acid rare earth salt precipitate and the first filtrate to achieve rare earth recovery; analysis showed that the rare earth recovery rate was 95% and the purity of the rare earth oxalate was 99.3%.
[0076] Add ethylhexyl phosphate mono-2-ethylhexyl ester extract (the volume ratio of ethylhexyl phosphate mono-2-ethylhexyl ester extract to the first filtrate is 2.5:1) to the first filtrate, extract for 50 minutes to obtain a vanadium-rich extract and an extract residue; evaporate the vanadium-rich extract at 100° C. for 4 hours and roast at 580° C. for 6 hours to obtain vanadium pentoxide, thereby realizing vanadium recovery; analysis shows that the vanadium recovery rate is 96% and the vanadium pentoxide concentration is 99.4%.
[0077] A sodium hydroxide solution having a sodium hydroxide concentration of 2.5 wt % is added to the extract residue (aqueous phase) to adjust the pH value to 9, thereby generating a mixed precipitate of aluminum hydroxide and nickel hydroxide. After filtering, the sodium hydroxide solution is continuously added to the precipitate and the pH value is adjusted to 12.5 by stirring, and then filtered again. The precipitate is nickel hydroxide, and the filtrate is a sodium aluminate solution, thereby realizing the recovery of nickel and aluminum. Analysis shows that the recovery rates of nickel and aluminum are 96% and 96% respectively, the purity of nickel hydroxide is 99.3%, and the purity of sodium aluminate is 99.5%;
[0078] Transfer material B2 to a polytetrafluoroethylene-lined autoclave (II), inject 1.5kg HF solution with a concentration of 40wt%, react at 50℃ for 0.3h, and input the gas produced by the reaction into another polytetrafluoroethylene-lined autoclave (III) filled with 15kg sodium hydroxide solution with a concentration of 20wt% through a one-way valve, and react at 90℃ for 1.5h. After the reaction, separate the product in the reactor (III) into solid and liquid to obtain solid sodium fluoride and crude sodium silicate liquid; the crude sodium silicate liquid is concentrated at 105℃ for 1h, adjusted to pH 12.2 with alkali solution, and then filtered to obtain 1.9kg sodium silicate solution product with a modulus of 2 and a SiO2 mass concentration of 21wt%. After analysis and calculation, the silicon recovery rate is 96% and the purity of sodium silicate is 99.7%.
[0079] Example 3
[0080] This embodiment provides a method for recovering silicon and metals from spent catalytic cracking / catalytic cracking catalysts, wherein the method comprises:
[0081] 1.0 kg of the spent catalytic cracking / cracking catalyst 3 was subjected to physical sand milling to obtain material A3 with an average particle size of 5 μm.
[0082] Transfer material A3 to a polytetrafluoroethylene lined reactor (I), add 1.5 kg of 1.5 mol / L hydrochloric acid solution, react at 70°C for 20 h, and separate the product obtained by the reaction into a liquid phase leaching solution and a solid phase material B3; wherein rare earth, vanadium, nickel, and aluminum elements in the spent catalytic cracking / cracking catalyst are dissolved in the leaching solution, and silicon remains in material B3. Material B3 is a loose microsphere with a silicon content of 99.1 wt% and a porosity of 0.94 cm 3 / g, and the total mass content of rare earth, aluminum, nickel and vanadium is 0.9wt%.
[0083] 0.12 kg of oxalic acid solution with an oxalic acid concentration of 0.5 mol / L was added to the leaching solution, and the pH value was adjusted to 2.1 with ammonia water to generate oxalic acid rare earth salt precipitate, which was filtered to obtain the oxalic acid rare earth salt precipitate and the first filtrate, thereby realizing rare earth recovery; analysis showed that the rare earth recovery rate was 96% and the purity of the rare earth oxalate was 99.2%.
[0084] Add ethylhexyl phosphate mono-2-ethylhexyl ester extract (the volume ratio of ethylhexyl phosphate mono-2-ethylhexyl ester extract to the first filtrate is 1.5:1) to the first filtrate, extract for 70 minutes to obtain a vanadium-rich extract and an extract residue; evaporate the vanadium-rich extract at 100° C. for 4 hours and roast at 580° C. for 6 hours to obtain vanadium pentoxide, thereby realizing vanadium recovery; analysis shows that the vanadium recovery rate is 95% and the vanadium pentoxide concentration is 99.5%.
[0085] A sodium hydroxide solution having a sodium hydroxide concentration of 2.5 wt % is added to the extract residue (aqueous phase) to adjust the pH value to 10, thereby generating a mixed precipitate of aluminum hydroxide and nickel hydroxide. After filtering, the sodium hydroxide solution is continuously added to the precipitate and the pH value is adjusted to 12.8 by stirring, and then filtered again. The precipitate is nickel hydroxide, and the filtrate is a sodium aluminate solution, thereby realizing the recovery of nickel and aluminum. According to analysis, the recovery rates of nickel and aluminum are 95% and 96% respectively, the purity of nickel hydroxide is 99.5%, and the purity of sodium aluminate is 99.2%;
[0086] Transfer material B3 to a polytetrafluoroethylene lined autoclave (II), inject 2.4kg HF solution with a concentration of 25wt%, react at 65℃ for 0.6h, and input the gas produced by the reaction into another polytetrafluoroethylene lined autoclave (III) filled with 12.5kg sodium hydroxide solution with a concentration of 24wt% through a one-way valve, and react at 95℃ for 1.2h. After the reaction, separate the product in the autoclave (III) into solid and liquid to obtain solid sodium fluoride and crude sodium silicate liquid; the crude sodium silicate liquid is concentrated at 105℃ for 1h, adjusted to pH 12.5 with alkali solution, and then filtered to obtain 2.0kg of sodium silicate solution product with a modulus of 1.5 and a SiO2 mass concentration of 23wt%. After analysis and calculation, the silicon recovery rate is 96% and the purity of sodium silicate is 99.6%.
[0087] Example 4
[0088] This embodiment provides a method for recovering silicon and metals from spent catalytic cracking / catalytic cracking catalysts, wherein the method comprises:
[0089] 1.0 kg of spent catalytic cracking / cracking catalyst 4 was subjected to physical sand milling to obtain material A4 with an average particle size of 12 μm.
[0090] Transfer material A4 to a polytetrafluoroethylene lined reactor (I), add 1.5 kg of 1 mol / L hydrochloric acid solution, react at 75°C for 15 h, and separate the product obtained by the reaction into a liquid phase leachate and a solid phase material B4; wherein rare earth, vanadium, nickel, and aluminum elements in the spent catalytic cracking / cracking catalyst are dissolved in the leachate, and silicon remains in material B4. Material B4 is a loose microsphere with a silicon content of 99.3 wt% and a porosity of 1.0 cm 3 / g, and the total mass content of rare earth, aluminum, nickel and vanadium is 0.7wt%.
[0091] 0.18 kg of oxalic acid solution with an oxalic acid concentration of 0.35 mol / L was added to the leaching solution, and the pH value was adjusted to 2.3 with ammonia water to generate oxalic acid rare earth salt precipitate, which was filtered to obtain the oxalic acid rare earth salt precipitate and the first filtrate to achieve rare earth recovery; analysis showed that the rare earth recovery rate was 95% and the purity of the rare earth oxalate was 99.6%.
[0092] Add di(2-ethylhexyl) phosphate extract (the volume ratio of di(2-ethylhexyl) phosphate extract to the first filtrate is 3:1) to the first filtrate, extract for 70 minutes to obtain a vanadium-rich extract and an extract residue; evaporate the vanadium-rich extract at 100° C. for 4 hours and roast at 580° C. for 6 hours to obtain vanadium pentoxide, thereby recovering vanadium; analysis shows that the vanadium recovery rate is 97% and the vanadium pentoxide concentration is 99.5%.
[0093] A sodium hydroxide solution having a sodium hydroxide concentration of 2.5 wt % is added to the extract residue (aqueous phase) to adjust the pH value to 7, thereby generating a mixed precipitate of aluminum hydroxide and nickel hydroxide. After filtering, the sodium hydroxide solution is continuously added to the precipitate and the pH value is adjusted to 12.6 by stirring, and then filtered again. The precipitate is nickel hydroxide, and the filtrate is a sodium aluminate solution, thereby realizing the recovery of nickel and aluminum. Analysis shows that the recovery rates of nickel and aluminum are 95% and 97% respectively, the purity of nickel hydroxide is 99.5%, and the purity of sodium aluminate is 99.4%;
[0094] Transfer material B4 to a polytetrafluoroethylene-lined autoclave (II), inject 2kg HF solution with a concentration of 30wt%, react at 40℃ for 0.7h, and input the gas produced by the reaction into another polytetrafluoroethylene-lined autoclave (III) filled with 12.5kg sodium hydroxide solution with a concentration of 24wt% through a one-way valve, and react at 85℃ for 1.5h. After the reaction, separate the product in the autoclave (III) into solid and liquid to obtain solid sodium fluoride and crude sodium silicate liquid; the crude sodium silicate liquid is concentrated at 105℃ for 1h, adjusted to pH 12.7 with alkali solution, and then filtered to obtain 2.2kg of sodium silicate solution product with a modulus of 2.5 and a SiO2 mass concentration of 19wt%. After analysis and calculation, the silicon recovery rate is 97% and the purity of sodium silicate is 99.5%.
[0095] Comparative Example 1
[0096] This comparative example provides a method for recovering silicon from spent catalytic cracking / catalytic cracking catalyst, wherein the method comprises:
[0097] 1.0 kg of spent catalytic cracking / cracking catalyst 1 was subjected to physical sand milling to obtain material A1 with an average particle size of 10 μm.
[0098] Transfer material A1 to a polytetrafluoroethylene lined reactor (I), add 1.5 kg of 3 mol / L hydrochloric acid solution, react at 90°C for 10 h, and separate the product obtained by the reaction into a liquid phase leachate and a solid phase material B1; wherein rare earth, vanadium, nickel, and aluminum elements in the spent catalytic cracking / cracking catalyst are dissolved in the leachate, and silicon remains in material B1. Material B1 is a loose microsphere with a silicon content of 99.0 wt% and a porosity of 0.95 cm 3 / g, and the total mass content of rare earth, aluminum, nickel and vanadium is 1.0wt%.
[0099] Transfer material B1 to a polytetrafluoroethylene-lined autoclave (II), inject 3kg of sulfuric acid solution with a concentration of 20wt% H2SO4, react at 60℃ for 0.5h, and input the gas produced by the reaction into another polytetrafluoroethylene-lined autoclave (III) filled with 20kg of sodium hydroxide solution with a concentration of 15wt% sodium hydroxide through a one-way valve, and react at 80℃ for 1h. After the reaction, separate the product in the reactor (III) into solid and liquid to obtain solid sodium fluoride and crude sodium silicate liquid; the crude sodium silicate liquid is concentrated at 105℃ for 1h, adjusted to pH 12 with alkali solution, and then filtered to obtain 2.6kg of sodium silicate solution product with a modulus of 3 and a SiO2 mass concentration of 4wt%. After analysis and calculation, the silicon recovery rate is 23%.
[0100] Comparative Example 2
[0101] This comparative example provides a method for recovering silicon from spent catalytic cracking / catalytic cracking catalyst, wherein the method comprises:
[0102] 1.0 kg of spent catalytic cracking / cracking catalyst 2 was subjected to physical sand milling to obtain material A2 with an average particle size of 15 μm.
[0103] Transfer material A2 to a polytetrafluoroethylene lined reactor (I), add 1.5 kg of 2 mol / L hydrochloric acid solution, react at 80°C for 12 h, and separate the product obtained by the reaction into a liquid phase leachate and a solid phase material B2; wherein rare earth, vanadium, nickel, and aluminum elements in the spent catalytic cracking / cracking catalyst are dissolved in the leachate, and silicon remains in material B2. Material B2 is a loose microsphere with a silicon content of 98.8 wt% and a porosity of 0.97 cm 3 / g, and the total mass content of rare earth, aluminum, nickel and vanadium is 1.2wt%.
[0104] Transfer material B2 to a polytetrafluoroethylene-lined autoclave (II), inject 1.5kg HNO3 nitric acid solution with a concentration of 40wt%, react at 50℃ for 0.3h, and input the gas produced by the reaction into another polytetrafluoroethylene-lined autoclave (III) filled with 15kg sodium hydroxide solution with a concentration of 20wt% through a one-way valve, and react at 90℃ for 1.5h. After the reaction, separate the product in the reactor (III) into solid and liquid to obtain solid sodium fluoride and crude sodium silicate liquid; the crude sodium silicate liquid is concentrated at 105℃ for 1h, adjusted to pH 12.2 with alkali solution, and then filtered to obtain 1.9kg sodium silicate solution product with a modulus of 2 and a SiO2 mass concentration of 4.1wt%. After analysis and calculation, the silicon recovery rate is 19%.
[0105] Comparative Example 3
[0106] This comparative example provides a method for recovering silicon from spent catalytic cracking / catalytic cracking catalyst, wherein the method comprises:
[0107] 1.0 kg of spent catalytic cracking / cracking catalyst 1 was subjected to physical sand milling to obtain material A1 with an average particle size of 10 μm.
[0108] Transfer material A1 to a polytetrafluoroethylene lined reactor (I), add 1.5 kg of 3 mol / L hydrochloric acid solution, react at 90°C for 10 h, and separate the product obtained by the reaction into a liquid phase leachate and a solid phase material B1; wherein rare earth, vanadium, nickel, and aluminum elements in the spent catalytic cracking / cracking catalyst are dissolved in the leachate, and silicon remains in material B1. Material B1 is a loose microsphere with a silicon content of 99.0 wt% and a porosity of 0.95 cm 3 / g, and the total mass content of rare earth, aluminum, nickel and vanadium is 1.0wt%.
[0109] Transfer material B1 to a polytetrafluoroethylene-lined autoclave (II), inject 20kg of HF solution with a concentration of 3wt%, react at 60°C for 0.5h, and input the gas produced by the reaction into another polytetrafluoroethylene-lined autoclave (III) filled with 20kg of sodium carbonate solution with a concentration of 15wt% through a one-way valve, react at 80°C for 1h. After the reaction, separate the product in the autoclave (III) into solid and liquid to obtain silicic acid and sodium fluorosilicate precipitate. After analysis and calculation, the silicon recovery rate is 59%.
[0110] Comparative Example 4
[0111] This comparative example provides a method for recovering silicon from spent catalytic cracking / catalytic cracking catalyst, wherein the method comprises:
[0112] 1.0 kg of spent catalytic cracking / cracking catalyst 1 was subjected to physical sand milling to obtain material A1 with an average particle size of 10 μm.
[0113] Transfer material A1 to a polytetrafluoroethylene lined reactor (I), add 1.5 kg of 3 mol / L hydrochloric acid solution, react at 90°C for 10 h, and separate the product obtained by the reaction into a liquid phase leachate and a solid phase material B1; wherein rare earth, vanadium, nickel, and aluminum elements in the spent catalytic cracking / cracking catalyst are dissolved in the leachate, and silicon remains in material B1. Material B1 is a loose microsphere with a silicon content of 99.0 wt% and a porosity of 0.95 cm 3 / g, and the total mass content of rare earth, aluminum, nickel and vanadium is 1.0wt%.
[0114] Transfer material B1 to a polytetrafluoroethylene-lined autoclave (II), inject 20kg HF solution with a concentration of 3wt%, react at 60℃ for 0.5h, and input the gas produced by the reaction into another polytetrafluoroethylene-lined autoclave (III) filled with 20kg sodium hydroxide solution with a concentration of 15wt% through a one-way valve, and react at 80℃ for 1h. After the reaction, separate the product in the autoclave (III) into solid and liquid to obtain solid sodium fluoride and crude sodium silicate liquid; the crude sodium silicate liquid is concentrated at 105℃ for 1h, adjusted to pH 12 with alkali solution, and then filtered to obtain 2.6kg sodium silicate solution product with a modulus of 3 and a SiO2 mass concentration of 9wt%. After analysis and calculation, the silicon recovery rate is 51%.
[0115] Comparative Example 5
[0116] This comparative example provides a method for recovering silicon from spent catalytic cracking / catalytic cracking catalyst, wherein the method comprises:
[0117] 1.0 kg of spent catalytic cracking / cracking catalyst 2 was subjected to physical sand milling to obtain material A2 with an average particle size of 15 μm.
[0118] Transfer material A2 to a polytetrafluoroethylene lined reactor (I), add 1.5 kg of 2 mol / L hydrochloric acid solution, react at 80°C for 12 h, and separate the product obtained by the reaction into a liquid phase leachate and a solid phase material B2; wherein rare earth, vanadium, nickel, and aluminum elements in the spent catalytic cracking / cracking catalyst are dissolved in the leachate, and silicon remains in material B2. Material B2 is a loose microsphere with a silicon content of 98.8 wt% and a porosity of 0.97 cm 3 / g, and the total mass content of rare earth, aluminum, nickel and vanadium is 1.2wt%.
[0119] Transfer material B2 to a polytetrafluoroethylene-lined autoclave (II), inject 1.5kg of HF solution with a concentration of 40wt%, react at 50℃ for 0.3h, and input the gas produced by the reaction into another polytetrafluoroethylene-lined autoclave (III) filled with 100kg of sodium hydroxide solution with a concentration of 3wt% through a one-way valve, and react at 90℃ for 1.5h. After the reaction, separate the product in the reactor (III) into solid and liquid to obtain solid sodium fluoride and crude sodium silicate liquid; the crude sodium silicate liquid is concentrated at 105℃ for 1h, adjusted to pH 12.2 with alkali solution, and then filtered to obtain 1.9kg of sodium silicate solution product with a modulus of 2 and a SiO2 mass concentration of 14wt%. After analysis and calculation, the silicon recovery rate is 63%.
[0120] Comparative Example 6
[0121] This comparative example provides a method for recovering silicon and metals from spent catalytic cracking / catalytic cracking catalysts, wherein the method comprises:
[0122] 1.0 kg of spent catalytic cracking / cracking catalyst 1 was subjected to physical sand milling to obtain material A1 with an average particle size of 10 μm.
[0123] Transfer material A1 to a polytetrafluoroethylene-lined reactor (I), add 1.5 kg of oxalic acid solution with a concentration of 3 mol / L oxalic acid, and react at 90°C for 10 h. The product obtained by the reaction is subjected to solid-liquid separation to obtain a liquid phase leachate and a solid phase material C1; the silicon content of material C1 is 61 wt%, and the porosity is 0.38 cm 3 / g, the total mass content of rare earth, aluminum, nickel and vanadium is 38.9wt%.
[0124] 0.2 kg of oxalic acid solution with an oxalic acid concentration of 0.3 mol / L was added to the leaching solution, and the pH value was adjusted to 2 with ammonia water to generate oxalic acid rare earth salt precipitate, which was filtered to obtain the oxalic acid rare earth salt precipitate and the first filtrate to achieve rare earth recovery; analysis showed that the rare earth recovery rate was 1%.
[0125] Add di(2-ethylhexyl) phosphate extract (the volume ratio of di(2-ethylhexyl) phosphate extract to the first filtrate is 2:1) to the first filtrate, extract for 60 minutes to obtain a vanadium-rich extract and an extract residue; evaporate the vanadium-rich extract at 100° C. for 4 hours and roast at 580° C. for 6 hours to obtain vanadium pentoxide, thereby recovering vanadium; analysis shows that the vanadium recovery rate is 94%.
[0126] A sodium hydroxide solution having a sodium hydroxide concentration of 2.5 wt% is added to the extract residue (aqueous phase) to adjust the pH value to 8, thereby generating a mixed precipitate of aluminum hydroxide and nickel hydroxide. After filtering, the sodium hydroxide solution is continuously added to the precipitate and the pH value is adjusted to 13 by stirring, and then filtered again. The precipitate is nickel hydroxide, and the filtrate is a sodium aluminate solution, thereby realizing the recovery of nickel and aluminum. After analysis, the recovery rates of nickel and aluminum are 2% and 4%, respectively.
[0127] Transfer material C1 to a polytetrafluoroethylene-lined autoclave (II), inject 3kg HF solution with a concentration of 20wt%, react at 60℃ for 0.5h, and input the gas produced by the reaction into another polytetrafluoroethylene-lined autoclave (III) filled with 20kg sodium hydroxide solution with a concentration of 15wt% through a one-way valve, and react at 80℃ for 1h. After the reaction, separate the product in the autoclave (III) into solid and liquid to obtain solid sodium fluoride and crude sodium silicate liquid; the crude sodium silicate liquid is concentrated at 105℃ for 1h, adjusted to pH 12 with alkali solution, and then filtered to obtain 2.6kg sodium silicate solution product with a modulus of 3 and a SiO2 mass concentration of 4.8wt%. After analysis and calculation, the silicon recovery rate is 27%.
[0128] Comparative Example 7
[0129] This comparative example provides a method for recovering silicon and metals from spent catalytic cracking / catalytic cracking catalysts, wherein the method comprises:
[0130] 1.0 kg of spent catalytic cracking / cracking catalyst 1 was subjected to physical sand milling to obtain material A1 with an average particle size of 10 μm.
[0131] Transfer material A1 to a polytetrafluoroethylene-lined reactor (I), add 1.5 kg of 3 mol / L sulfuric acid solution of H2SO4, and react at 90°C for 10 h. The product obtained by the reaction is separated into a liquid phase leaching liquid and a solid phase material D1 by solid-liquid separation; the silicon content of material D1 is 92 wt%, and the porosity is 0.65 cm3 / g, the total mass content of rare earth, aluminum, nickel and vanadium is 7.9wt%.
[0132] 0.2 kg of oxalic acid solution with an oxalic acid concentration of 0.3 mol / L was added to the leaching solution, and the pH value was adjusted to 2 with ammonia water to generate oxalic acid rare earth salt precipitate, which was filtered to obtain the oxalic acid rare earth salt precipitate and the first filtrate to achieve rare earth recovery; analysis showed that the rare earth recovery rate was 1.5%.
[0133] Add di(2-ethylhexyl) phosphate extract (the volume ratio of di(2-ethylhexyl) phosphate extract to the first filtrate is 2:1) to the first filtrate, extract for 60 minutes to obtain a vanadium-rich extract and an extract residue; evaporate the vanadium-rich extract at 100° C. for 4 hours and calcine at 580° C. for 6 hours to obtain vanadium pentoxide, thereby recovering vanadium; analysis shows that the vanadium recovery rate is 3%.
[0134] A sodium hydroxide solution having a sodium hydroxide concentration of 2.5 wt % is added to the extract residue (aqueous phase) to adjust the pH value to 8, thereby generating a mixed precipitate of aluminum hydroxide and nickel hydroxide. After filtering, the sodium hydroxide solution is continuously added to the precipitate and the pH value is adjusted to 13 by stirring, and then filtered again. The precipitate is nickel hydroxide, and the filtrate is a sodium aluminate solution, thereby realizing the recovery of nickel and aluminum. The nickel and aluminum recovery rates are 93% and 91% respectively after analysis.
[0135] Transfer material D1 to a polytetrafluoroethylene-lined autoclave (II), inject 3kg HF solution with a concentration of 20wt%, react at 60℃ for 0.5h, and input the gas produced by the reaction into another polytetrafluoroethylene-lined autoclave (III) filled with 20kg sodium hydroxide solution with a concentration of 15wt% through a one-way valve, and react at 80℃ for 1h. After the reaction, separate the product in the autoclave (III) into solid and liquid to obtain solid sodium fluoride and crude sodium silicate liquid; the crude sodium silicate liquid is concentrated at 105℃ for 1h, adjusted to pH 12 with alkali solution, and then filtered to obtain 2.6kg sodium silicate solution product with a modulus of 3 and a SiO2 mass concentration of 9.6wt%. After analysis and calculation, the silicon recovery rate is 55%.
[0136] Comparative Example 8
[0137] This comparative example provides a method for recovering silicon and metals from spent catalytic cracking / catalytic cracking catalysts, wherein the method comprises:
[0138] 1.0 kg of spent catalytic cracking / cracking catalyst 1 was subjected to physical sand milling to obtain material A1 with an average particle size of 10 μm.
[0139] Transfer material A1 to a polytetrafluoroethylene lined autoclave (II), inject 3kg HF solution with a concentration of 20wt%, react at 60℃ for 0.5h, and input the gas produced by the reaction into another polytetrafluoroethylene lined autoclave (III) filled with 20kg sodium hydroxide solution with a concentration of 15wt% through a one-way valve, and react at 80℃ for 1h. After the reaction, separate the solid and liquid of the product in the autoclave (III) to obtain solid sodium fluoride and crude sodium silicate liquid; the crude sodium silicate liquid is concentrated at 105℃ for 1h, adjusted to pH 12 with alkali solution, and then filtered to obtain 2.6kg sodium silicate solution product with a modulus of 3 and a SiO2 mass concentration of 6.5wt%. After analysis and calculation, the silicon recovery rate is 37%.
[0140] Comparative Example 9
[0141] This comparative example provides a method for recovering silicon and metals from spent catalytic cracking / catalytic cracking catalysts, wherein the method comprises:
[0142] 1.0 kg of spent catalytic cracking / cracking catalyst 1 was subjected to physical sand milling to obtain material A1 with an average particle size of 10 μm.
[0143] The material-lined reactor A1 was transferred to polytetrafluoroethylene (I), and 1.5 kg of 5 mol / L hydrochloric acid solution was added. The reaction was carried out at 75°C for 10 h. The product obtained by the reaction was separated into a liquid phase leaching liquid and a solid phase material E1. The silicon content of the material E1 was 90 wt%, and the porosity was 0.56 cm 3 / g, the total mass content of rare earth, aluminum, nickel and vanadium is 9.7wt%.
[0144] The hydrochloric acid leaching solution is first adjusted to pH=1.4 with sodium hydroxide solution, and hydrogen peroxide is added for heating reaction; the reaction conditions are: temperature 60°C, reaction time 30min. 50% (v / v) di(2,4,4-trimethylpentyl)phosphinate heptane solution is used as an extractant for extraction; the extraction conditions are: the organic phase and the aqueous phase ratio (O / A) is 1:1, the extraction temperature is 25°C, and the extraction time is 45min; then the loaded organic phase is stripped with an ammonia solution to obtain a vanadium product; the stripping conditions are: ammonia solution concentration 15wt%, pH=8.2, stripping time 60min, phase ratio 3:1. The vanadium recovery rate is analyzed to be 89%. The hydrochloric acid leaching solution after extraction is adjusted to pH=3.8 with sodium hydroxide solution, filtered, and a precipitate containing aluminum hydroxide and the remaining hydrochloric acid extract are obtained. The remaining hydrochloric acid leaching solution is first adjusted to pH 7.5 with sodium hydroxide solution, and oxalic acid solution is used for precipitation reaction, filtered, and rare earth products and nickel-containing filtrate are obtained respectively; the reaction conditions are: the amount of oxalic acid solution added is 2 times the theoretical reaction amount of rare earth, the temperature is controlled at 70°C when adding, the stirring time is 90 minutes, and it is allowed to stand for 60 minutes for precipitation. The rare earth recovery rate is 85% after analysis; sodium sulfide 1 times the theoretical reaction amount is added to the nickel-containing filtrate, filtered, and nickel sulfide is obtained. The vanadium recovery rate is 82% after analysis.
[0145] Transfer material E1 to a polytetrafluoroethylene-lined autoclave (II), inject 3kg HF solution with a concentration of 20wt%, react at 60℃ for 0.5h, and input the gas produced by the reaction into another polytetrafluoroethylene-lined autoclave (III) filled with 20kg sodium hydroxide solution with a concentration of 15wt% through a one-way valve, and react at 80℃ for 1h. After the reaction, separate the product in the autoclave (III) into solid and liquid to obtain solid sodium fluoride and crude sodium silicate liquid; the crude sodium silicate liquid is concentrated at 105℃ for 1h, adjusted to pH 12 with alkali solution, and then filtered to obtain 2.6kg sodium silicate solution product with a modulus of 3 and a SiO2 mass concentration of 14.2wt%. After analysis and calculation, the silicon recovery rate is 81%.
Claims
1. A method for recovering silicon and metals from spent catalytic cracking / catalytic cracking catalysts, wherein: The method includes: The spent catalytic cracking / catalytic cracking catalyst is treated with hydrochloric acid having a concentration of 1-3 mol / L at 60-120° C., and a leachate and loose microspheres are obtained by solid-liquid separation; Utilizing leachate for metal recovery; The loose microspheres react with a hydrofluoric acid solution, and the generated gas is passed into a sodium hydroxide solution for reaction, and the solid phase is removed from the product obtained by the reaction to obtain liquid sodium silicate; wherein the mass concentration of HF in the hydrofluoric acid solution is 5-47%, and the mass concentration of sodium hydroxide in the sodium hydroxide solution is 5-40%.
2. The method according to claim 1, wherein: Metal recovery using leachate includes: The leaching solution is mixed with the oxalic acid solution and the pH value is adjusted to 1.6-2.3 by using an alkali solution for reaction, and the oxalic acid rare earth salt precipitate and the first filtrate are obtained through solid-liquid separation to realize rare earth recovery; The first filtrate is subjected to extraction to recover vanadium, thereby obtaining a vanadium-rich extract and an extraction residue, thereby achieving vanadium recovery; The pH value of the extract residue is adjusted to 6-10 by using alkaline solution to react, and a mixed precipitate of aluminum hydroxide and nickel hydroxide is obtained by solid-liquid separation; Alkali solution is added to the mixed precipitate of aluminum hydroxide and nickel hydroxide to adjust the pH value to 12-13 for reaction, and nickel hydroxide precipitate and aluminate solution are obtained through solid-liquid separation to realize the recovery of nickel and aluminum.
3. The method according to claim 2, wherein: The method also includes: evaporating the vanadium-rich extract to dryness, pyrolyzing and roasting to obtain vanadium pentoxide.
4. The method according to claim 2, wherein: The concentration of oxalic acid in the oxalic acid solution is 0.1-0.5 mol / L.
5. The method according to claim 2, wherein: The alkali solution used in the process of adjusting the pH value to 1.6-2.3 includes ammonia water and / or sodium hydroxide solution; and / or The alkali solution used in the process of adjusting the pH value of the residual extract to 6-10 comprises at least one of a sodium hydroxide solution, a potassium hydroxide solution and an ammonia solution; and / or The alkali solution used in the process of adding alkali solution to the mixed precipitate of aluminum hydroxide and nickel hydroxide to adjust the pH value to 12-13 includes at least one of sodium hydroxide solution, potassium hydroxide solution and ammonia water.
6. The method according to claim 1, wherein: The extracting liquid used in the process of extracting and recovering vanadium from the first filtrate is an organic extracting liquid; Preferably, the extract may include, but is not limited to, at least one of (2-ethylhexyl) phosphate, ethylhexyl mono-2-ethylhexyl phosphate; Preferably, in the process of extracting and recovering vanadium from the first filtrate, the volume ratio of the extract to the first filtrate is 1-3:
1.
7. The method according to claim 1, wherein: Taking the total mass of the waste catalytic cracking / catalytic cracking catalyst as 100%, the mass content of SiO2 in the waste catalytic cracking / catalytic cracking catalyst is 40-50wt%, and the mass content of SiO2, Al2O3, RE2O3, Ni and V is not less than 99.5wt%; Preferably, based on the total mass of the spent catalytic cracking / catalytic cracking catalyst as 100%, the mass content of SiO2 in the spent catalytic cracking / catalytic cracking catalyst is 40-50wt%, the mass content of Al2O3 is 40-50wt%, the mass content of RE2O3 is 0.1-10wt%, the mass content of Ni is 0.01-2wt%, and the mass content of V is 0.01-2wt%.
8. The method according to claim 1, wherein: Before the spent catalytic cracking / catalytic cracking catalyst is subjected to hydrochloric acid leaching treatment, it is crushed into a material with a particle size of 1-15 μm and then subjected to hydrochloric acid leaching treatment.
9. The method according to claim 1, wherein: The silicon oxide content of the loose microspheres is not less than 98.5wt% and the porosity is not less than 0.9cm 3 / g, the total mass content of rare earth, aluminum, nickel and vanadium in the loose microspheres is less than 1.5wt%.
10. The method according to claim 1, wherein: The mass concentration of HF in the hydrofluoric acid solution is 15-25%.
11. The method according to claim 1, wherein: The mass concentration of sodium hydroxide in the sodium hydroxide solution is 10-25%.
12. The method according to claim 1, wherein: The temperature for the reaction between the loose microspheres and the hydrofluoric acid solution is 20-80°C.
13. The method according to claim 1, wherein: The generated gas is passed into the sodium hydroxide solution for reaction at a temperature of 60-100°C.
14. The method according to claim 1, wherein: The method further comprises: removing the solid phase to obtain the liquid sodium silicate, concentrating, adjusting with alkali solution and re-filtering to obtain a sodium silicate solution product that meets the requirements of modulus and concentration; Preferably, the modulus of the sodium silicate solution product is 1.5-3.5; Preferably, the SiO2 mass concentration in the sodium silicate solution product is 15-25wt%.
Citation Information
Cited By
Method for graded utilization of waste catalytic cracking / catalytic cracking catalyst
CN119972762A
A method for staged utilization of spent catalytic cracking / catalytic cracking catalyst
CN119972762B